Comparative Analysis of Video and Demonstration Methods in Enhancing Basic Life Support (BLS) Knowledge and Skills among Youth in Surabaya, Indonesia - Sri Rahayu Estiningtyas; Dwi Utari W; Joko Suwito; Adin Mu’afiro; Christine I Reyes (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Tim Gerak Cepat (TGC) is one of Surabaya's command centers that serves various real time reports related to medical emergencies, one of which is cardiac arrest. Not every time TGC can arrive to provide rapid assistance, which can be influenced by inadequate road access to the location. This causes the provision of help including help for victims of cardiac arrest to be delayed. The objectives is to analyze the video effectiveness and demonstration methods on the ability to perform BLS on youth organizations RW 04 Ambengan Tengah Surabaya. Using pre-experimental using Two Group Pretest-Posttest Design. The study population was all youth organizations in RW 04 Ambengan Tengah Surabaya. The research sample amounted to 36 adolescents who were selected by random sampling by meeting the inclusion criteria. The data analysis used was the Wilcoxon Signed Rank Test and Mann Whitney test. The Wilcoxon test showed that both methods could improve knowledge about BLS with a significance value of 0.000 (p<0.05) and could improve adolescents' skills in performing BLS with a significance value in the video group of 0.002 while in the demonstration group it was 0.001 (p<0.05). The different results score pre-test post-test knowledge of both methods with the Mann Whitney test showed a significance value in 0.129 (p <0.05) while the skill different score pre-test post-test had a significance 0.500 (p>0.05) value . This shows that between the video and demonstration methods there is no significant difference.